Positioning FYR Macedonia for the Global Economy : The Impact of Reforms and Investment Promotion in the Automotive Components Manufacturing Sector - World Bank Group (World Bank, Washington, DC, 2018)
Over the last two decades, successive governments and business leaders in the former Yugoslav Republic of (FYR) Macedonia have been actively working to transform the country’s economy and put it on a higher, technology-based, growth trajectory. For a small, landlocked country with a limited domestic market and a weak industrial base, this requires building a private sector that is competitive, export oriented,and integrated into global value chains (GVCs). In FYR Macedonia, where 23.7 percent of the labor force is unemployed and 30.7 percent of the population lives on less than USD 5 a day (2016 data),creating an attractive, competitive, and export-oriented private sector—one that leverages the country’s proximity to developed European markets and world-class enterprises—has become a political and strategic economic objective of the highest priority. This report describes the parameters of an aggressive reform and investment promotion effort in FYR Macedonia that began a decade ago and moved the country’s manufacturing sector toward higher value added, technology-based production with a unique focus on automotive component manufacturing. Readers interested in learning how a small country located in the Balkans region with a-priori low potential was able to reform its institutions, promote itself, and attract foreign direct investment (FDI) should find it useful. So will readers that are interested in industry specific strategies that go beyond first generation business environment reforms. Much of the report is a look backwards, to describe the parameters of the program, how it was executed, and results that were achieved. However, future steps are also proposed. The program is still very much a work in progress, and while very real and significant gains have been made—much to the credit of the country—certain aspects of it could be improved. Parts of the program are also in the process of being reshaped to reach new objectives, many of them related to sustainability. How well the government of FYR Macedonia focuses on new objectives defined by this transitional shift and directs future resources to encourage the processes there to go forward, will be a determining factor in whether its companies, and the country as whole, will be able to take the economy to a new level of competitiveness.